OTH-09 Ferrous sulphate supplementation is associated with a change in the faecal metabolome. (June 2019) - Ahmed, Ammar; Hough, Rachael; Lewis, Stephen; Probert, Chris
Abstract : Introduction: Oral iron supplementation treats iron deficiency anaemia, but it may cause GI side effects. Iron influences the growth of specific gut bacteria and may lead to dysbiosis, which may contribute to the side effects. Previously, we have shown that oral iron worsens colitis in mice and causes a dysbiosis. Here we report the effect of ferrous sulphate supplementation on the human metabolome by quantifying changes in faecal volatile organic compounds (VOCs), for the first time. VOCs are part of the metabolome and reflect gut bacterial metabolism. We aimed to compare the faecal metabolome before and after ferrous sulphate supplementation. Methods: 77 faecal samples were collected from patients with iron deficiency anaemia, before treatment and after two months of therapy. Faecal headspace gases were analysed using gas chromatography–mass spectrometry: VOC identification involved matching mass spectra against the NIST Library. Univariate and multivariate analysis was performed on the VOCs found, including partial least squares regression (PLS-DA). Results: A significant change in abundance of 17 VOCs was found. Adjustment was made for the number of comparisons: one VOC was then shown to increase significantly. The median abundance of 2-pentylfuran changed four-fold (FDR adjusted P = 0.006) in patients taking ferrous sulphate for two months (figure 1A). Overall, a plot to illustrate the PLS-DA shows how the pre- and post-treatment samples differ (figure 1B). Though the abundance changed in 16 other VOCs–which included aldehydes, esters and ketones–their significance was lost after correction for multiple testing, which indicates that the study may be underpowered. Conclusions: The abundance of faecal 2-pentylfuran increases significantly during ferrous sulphate therapy. 2-pentylfuran is a metabolite of fungi. It remains to be seen whether ferrous sulphate directly acts on fungi or whether there is an interaction between iron and bacteria, and then between bacteria and fungi. It is very clear that faecal metabolites are influenced by ferrous sulphate supplementation.